A Cesàro-like Operator from Besov Spaces to Some Spaces of Analytic Functions - Sun, Fangmei; Ye, Fangqin; Zhou, Liuchang (Computational methods and function theory, 2025)
In this paper, for p>1 and s>1, we characterize completely the boundedness and compactness of a Cesàro-like operator from the Besov space Bp into a Banach space X between the mean Lipschitz space Λ1/ss and the Bloch space. In particular, for p=s=2, we complete a previous result from the literature.